Aminated epoxy cardanol glycidyl ether compatilizer as well as preparation and application thereof
Through the self-polymerization and grafting reaction of amino-epoxy cashewol glycidyl ether, a three-dimensional network structure is formed, which solves the problem of poor interface compatibility of bamboo fibers in 3D printing, and improves the mechanical properties and service stability of composite materials. , realizes thermoplastic processing of high-filled bamboo plastic composite materials and the preparation of high-performance 3D printing products.
Patent Information
- Application Number
- CN202411496901.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-24
AI Technical Summary
In the prior art, bamboo fibers have poor interfacial compatibility due to surface polarity and high water absorption during 3D printing, poor processing fluidity and mechanical properties, and the commonly used compatibility agents are in service stability in high temperature and humid environments. insufficient.
Aminolated epoxy cashewol glycidyl ether as a compatible agent, a three-dimensional network structure is formed through self-polymerization and grafting reaction, which enhances the intermolecular interaction force and migration resistance. It is used to modify the co-copy of bamboo fibers and polylactic acid. Mixture, improve interface compatibility and mechanical properties.
The uniform dispersion and interface compatibility of bamboo fibers and polylactic acid are achieved, and the service stability and thermal stability of composite materials are enhanced. The problem of high-filling thermoplastic processing of fibers is overcome, and the biodegradable bamboo with excellent mechanical properties is prepared. Plastic composite material.
Smart Images

Figure CN119285901A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic additives, and in particular to an amino epoxy cardanol glycidyl ether compatibilizer and a preparation method and application thereof. Background Art
[0002] PLA / bamboo fiber composites for fused deposition modeling (FDM) 3D printing filaments are environmentally sustainable, lightweight and high-strength, with unique appearance and texture and lower cost. With its flexible design and manufacturing capabilities, it can meet the needs of sophisticated manufacturing for complex structural parts and personalized and differentiated products, and has good commercial prospects. However, the application of continuous plant fiber reinforced composites in 3D printing technology is still rare. This is mainly because the large number of polar hydroxyl groups (alcoholic hydroxyl groups and phenolic hydroxyl groups) on the surface of bamboo fibers (BFs), strong water absorption and intermolecular forces make it less dispersible during thermoplastic processing; when melt blended with hydrophobic polylactic acid (PLA) resin, the interface compatibility is poor; the processing fluidity and mechanical properties are poor when preparing high-fiber-content composites, and problems such as broken wire and nozzle clogging occur during extrusion and 3D printing, which affect the dimensional stability and printing accuracy of the product.
[0003] Researchers have conducted extensive research on the performance modification of fiber-reinforced composites, mainly focusing on fiber surface treatment and polymer matrix modification. The purpose of fiber surface treatment is to reduce the surface polarity of the fiber and increase the surface roughness, thereby improving the interface bonding with the polymer matrix. It includes physical methods such as steam explosion and high-temperature carbonization and chemical methods such as alkali treatment and silane coupling agent treatment. However, physical methods have high requirements for equipment and high energy consumption; chemical methods have complicated steps and are difficult to achieve industrial production.
[0004] Directly introducing modifiers during the melt blending stage has become the first choice for the green and efficient preparation of modified new materials. Thermodynamically immiscible polymer blends are often effectively expanded by non-in-situ and in-situ reactive compatibilizers. Although non-in-situ reactive compatibilizers can enable fiber-reinforced composites to exhibit excellent physical properties and processing properties through physical effects such as reducing interfacial tension and strengthening interphase adhesion, during the thermoplasticization process, due to the lack of chemical reaction, the depolymerization and disentanglement of macromolecular chains are prone to occur; when the compatibilizer is excessive, agglomeration is prone to occur, forming a phase separation structure, and the expansion efficiency is low.
[0005] By using an in-situ reactive compatibilizer with reactive functional groups (anhydride, isocyanate, etc.), its low melt viscosity can be diffused to the surface of the blend in a short time and efficiently, and the active groups are used to react with the polar groups on the fiber surface and the terminal groups of the matrix to form a graft copolymer, thereby achieving the surface treatment of the fiber and the modification of the polymer matrix. However, there is often a problem of a short-term decrease in the mechanical properties of the composite material due to the migration of the compatibilizer molecules, and the service stability of the product in high temperature and humid environments cannot be ensured.
[0006] Therefore, it is urgent to develop a bio-based compatibilizer with high synthesis efficiency, high reactivity, good compatibility modification and migration resistance. Summary of the invention
[0007] The purpose of the present invention is to provide an amino epoxy cardanol glycidyl ether compatibilizer and its preparation and application to solve the problems existing in the above-mentioned prior art. The present invention uses epoxy cardanol glycidyl ether (NC514) as a raw material, initiates the self-polymerization of NC514 and introduces amino groups for grafting modification to form a three-dimensional network polymer, and increases the molecular weight of NC514 and the chemical sites that react with BFs and PLA to improve the interaction between molecules. The molecular structure of the compatibilizer is regulated by controlling the conditions of self-polymerization and grafting reaction. The adjustment of the molecular structure can enhance the service stability of the composite material while enhancing the migration resistance, thereby providing a promising strategy for realizing the thermoplastic processing of highly filled bamboo-plastic composite materials and the preparation of high-performance 3D printed products.
[0008] To achieve the above object, the present invention provides the following solutions:
[0009] One of the technical solutions of the present invention: an aminated epoxy cardanol glycidyl ether (abbreviated as NH2-NC514), the structural formula is:
[0010]
[0011] in, Represents -(CH2)6-(alkane chain).
[0012] Wherein, m is any natural number; n is any natural number.
[0013] The structural formula actually represents the repeating unit of the NH2-NC514 polymer, which reflects the chemical sites that can react (the structural formula of the chemical sites that can react is marked as Figure 1 The reaction site in the red box is in the same structure as poly-NC514 (the chemical site that can react is marked as shown in Figure 2The reaction site in the red box (shown in a) continues to react and connect, and the reaction site in the blue circle is connected with the hydrolyzed KH550 (the structural formula of the chemical site that can react is marked as Figure 2 The reaction sites in the blue circles in (b) continue to react and connect.
[0014] Technical solution 2 of the present invention: A method for preparing the above-mentioned aminated epoxy cardanol glycidyl ether comprises the following steps:
[0015] 3-aminopropyltriethoxysilane (KH550) is hydrolyzed to obtain hydrolyzed KH550;
[0016] The self-polymerization of epoxy cardanol glycidyl ether (NC514) was initiated by a cationic initiator to obtain poly-epoxy cardanol glycidyl ether (poly-NC514);
[0017] The poly-NC514 and the hydrolyzed KH550 are used as reactants to carry out a grafting reaction to obtain the amino epoxy cardanol glycidyl ether (NH2-NC514).
[0018] Furthermore, the KH550 The step of performing hydrolysis comprises: dissolving KH550 in an ethanol solution, and magnetically stirring for 30-90 minutes, preferably 30 minutes, to complete the hydrolysis reaction and obtain the hydrolyzed KH550.
[0019] Preferably, the volume fraction of the ethanol solution is 60%.
[0020] Preferably, the dissolution concentration of KH550 in the ethanol solution is 2 wt. % (ie, the concentration of KH550 in the mixed system after dissolution is 2 wt. %).
[0021] Preferably, the temperature of the hydrolysis reaction is room temperature.
[0022] Furthermore, the structural formula of the hydrolyzed KH550 is: (Right now Figure 2 b) in the above.
[0023] Furthermore, the step of initiating the self-polymerization of NC514 using a cationic initiator comprises:
[0024] The cationic initiator and NC514 are dissolved in a solvent and stirred vigorously for 5-10 minutes at room temperature to initiate the self-polymerization of NC514 to obtain the poly-NC514 (structural formula: Figure 2 (as shown in a in the figure).
[0025] Preferably, the solvent is a mixture of acetone, ethanol, xylene and n-butanol in a volume ratio of 7:3 or propylene glycol methyl ether, and acetone is most preferred. Acetone has a good dissolving effect as a solvent and evaporates quickly.
[0026] Preferably, the cationic initiator is boron trifluoride ethylamine complex (BF3NH2Et).
[0027] Preferably, the amount of the cationic initiator is 1-2 wt.% of the amount of NC514.
[0028] Preferably, the temperature of the self-polymerization is room temperature.
[0029] The chemical reaction formula for preparing poly-NC514 is as follows: Figure 3 NC514 and poly NC514 Both represent an alkane chain -(CH2)6-.
[0030] Depend on Figure 3 From the reaction equation, it can be seen that the protons generated by BF3NH2Et can induce the opening of the epoxy ring, thereby carrying out the self-polymerization of NC514 (or ESO).
[0031] Preferably, the weight average molecular weight of the poly-NC514 is 900-1500 g / mol.
[0032] Furthermore, the step of carrying out a grafting reaction using poly-NC514 and the hydrolyzed KH550 as reactants includes: dissolving the poly-NC514 in the hydrolyzed KH550, stirring for 30-60 minutes, completing a grafting reaction (amino grafting modification reaction), and obtaining the NH2-NC514.
[0033] Preferably, the mass ratio of the poly-NC514 to the hydrolyzed KH550 is 3-1:1-3, more preferably 3:1, 1:1 or 1:3.
[0034] Preferably, the temperature of the grafting reaction is room temperature.
[0035] Preferably, after the grafting reaction is completed, the process further comprises drying the grafting reaction product in a vacuum oven at 80° C. for 12 hours.
[0036] Preferably, the weight average molecular weight of the NH2-NC514 is 5000-12000 g / mol, more preferably 8000 g / mol.
[0037] The reaction conditions of the self-polymerization and grafting reactions will affect the molecular weight of the product NH2-NC514. By adjusting the reaction conditions of the self-polymerization (including the time of the self-polymerization reaction and the amount of the cationic initiator used), and the reaction conditions of the grafting reaction (including the amount ratio of poly-NC514 to hydrolyzed KH550 and the time of the grafting reaction), NH2-NC514 with any molecular weight in the range of 5000-12000 g / mol can be obtained.
[0038] Technical solution three of the present invention: Application of the above-mentioned amino epoxy cardanol glycidyl ether as a compatibilizer in the preparation of 3D printing composite materials.
[0039] Technical solution four of the present invention: A 3D printing composite material, wherein the raw materials include, by weight: 70 parts of PLA (polylactic acid), 30 parts of BFs (bamboo fiber) and 2-8 parts of a compatibilizer; the compatibilizer is the above-mentioned amino epoxy cardanol glycidyl ether.
[0040] NH2-NC514 is used as a compatibilizer for the matrix materials (PLA and BFs) of 3D printed composite materials, making the matrix materials have excellent interface compatibility, mechanical properties, processing properties and service stability.
[0041] Preferably, the amount of the compatibilizer is 4-8 parts.
[0042] Technical solution 5 of the present invention: A method for preparing the above-mentioned 3D printing composite material, comprising the following steps:
[0043] PLA, BFs and a compatibilizer are first mixed at room temperature and then mixed by internal kneading to obtain the 3D printing composite material.
[0044] Furthermore, the specific operation of the room temperature mixing is: stirring and mixing at a rotation speed of 60 rpm for 10-30 minutes at room temperature; the specific operation of the banburying mixing is: stirring and mixing at a rotation speed of 60 rpm for 8 minutes at 190°C.
[0045] Technical solution 6 of the present invention: A method for preparing a 3D printed product using the above-mentioned 3D printed composite material, comprising the following steps:
[0046] The 3D printing composite material is crushed and then melt-extruded to obtain thermoplastic filaments; the thermoplastic filaments are 3D printed to obtain 3D printed products.
[0047] Preferably, the temperature of the melt extrusion is 175-180° C.; and the diameter of the thermoplastic filament is 1.75±0.03 mm.
[0048] Furthermore, before the mixed material is crushed and melt-extruded, the crushed 3D printing composite material is vacuum-dried at 80° C. for 12 hours to remove residual moisture in the 3D printing composite material.
[0049] Preferably, the 3D printing is performed in an FDM printer, and the parameters of the FDM printer are set to: nozzle temperature 190-220°C, platform temperature 60-80°C, printing speed 40-80mm / s, layer thickness 0.05-0.25mm; the layer thickness is most preferably 0.1mm.
[0050] Technical solution seven of the present invention: a 3D printed product obtained by the above-mentioned preparation method.
[0051] The material properties of continuous plant fiber reinforced composite materials are not highly compatible with 3D printing technology, so the application of 3D printing technology is still rare. The present invention directly adds amino epoxy cardanol glycidyl ether that can be diffused to the surface of the blend in a short time and efficiently as a compatibilizer in melt blending, while realizing the surface treatment of the fiber and the modification of the polymer matrix, and preparing a fully bio-based degradable bamboo-plastic composite material (3D printing composite material) with excellent processing fluidity and mechanical properties. When the 3D printing composite material is used for 3D printing, the 3D printed product prepared by adjusting the nozzle temperature, printing layer height, printing speed and filling rate not only has excellent mechanical properties, thermal properties, appearance quality and processability, but also has excellent anti-aging performance and service stability.
[0052] The present invention discloses the following technical effects:
[0053] The present invention provides a novel bio-based compatibilizer, aminated epoxy cardanol glycidyl ether (NH2-NC514), for a PLA / BFs composite material. The present invention prepares a reactive migration-resistant compatibilizer NH2-NC514 having a three-dimensional network structure with high synthesis efficiency, high reaction activity, good compatibility modification and migration resistance by initiating self-polymerization of NC514 and introducing amino groups for grafting modification. The molecular weight of the compatibilizer and the chemical sites for reaction with BFs and PLA are increased to improve the interaction force between molecules. The molecular structure (molecular weight) of the compatibilizer is regulated by controlling the conditions of self-polymerization and grafting reactions. The adjustment of the molecular structure (molecular weight) can enhance the service stability of the composite material while enhancing the migration resistance. When the NH2-NC514 prepared by the present invention is used as a compatibilizer for PLA / BFs composite materials, the reaction of active groups such as epoxy, hydroxyl, and amino groups in the structure with polar groups on the surface of BFs and terminal groups of the PLA molecular chain can not only promote the effective dispersion of PLA and BFs and ensure the uniformity of the composite material; it can also enhance the interfacial compatibility, reduce interfacial tension, and improve the bonding strength through chemical reactions; it can also play a role in the crosslinking and curing process, build a stable three-dimensional network, enhance the mechanical and thermal stability of the composite material, and prepare a fully bio-based degradable bamboo-plastic composite material with excellent processing fluidity and mechanical properties. The above composite material is applied to 3D printing, and the prepared 3D printed products not only have excellent mechanical properties, thermal properties, appearance quality and processability, but also have excellent anti-aging properties and service stability. It overcomes the problem that high fiber filling cannot achieve thermoplastic processing and achieves the preparation of excellent and stable bamboo-plastic 3D printed products. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0055] Figure 1 is the structural formula of NH2-NC514;
[0056] Figure 2 is the structural formula of poly-NC514 and hydrolyzed KH550, wherein a is poly-NC514, and b is hydrolyzed KH550;
[0057] Figure 3 The chemical reaction formula for preparing poly-NC514 by self-polymerization;
[0058] Figure 4 The chemical reaction formula for preparing NH2-ESO by self-polymerization;
[0059] Figure 5 Reaction mechanism for preparing 3D printing composite materials;
[0060] Figure 6 The infrared spectra (FTIR) of NH2-NC514 prepared in Example 1, NH2-ESO prepared in Comparative Example 1, and raw materials NC514 and ESO;
[0061] Figure 7 The SEM images of BFs extracted from 3D printed composite materials prepared in Application Example 1, Comparative Application Examples 1 and 3, wherein (a)-(c) are surface SEM images of BFs (extracted from Comparative Application Example 3), BFs / 4NH2-ESO (extracted from Comparative Application Example 1) and BFs / 4NH2-NC514 (extracted from Application Example 1), respectively;
[0062] Figure 8 The curve-resolved XPS C1s spectra of BFs extracted from the 3D printed composite materials prepared in Application Examples 1-2 and Comparative Application Examples 1-3, wherein (a)-(e) are BFs (extracted from Comparative Application Example 3), BFs / 4NH2-ESO (extracted from Comparative Application Example 1), BFs / 4NH2-ESO (extracted from Comparative Application Example 2), BFs / 4NH2-NC514 (extracted from Application Example 1), and BFs / 4NH2-NC514 (extracted from Application Example 2), respectively;
[0063] Fig. 9 DSC secondary heating curves of the 3D printed composite materials prepared in Application Examples 1-2 and Comparative Application Examples 1-3;
[0064] Fig.10 DMA curves of 3D printed composite materials prepared in Application Examples 1-2 and Comparative Application Examples 1-3, wherein (a) is the storage modulus and (b) is the loss factor;
[0065] Fig.11 The rheological properties test curves of the 3D printed composite materials prepared in Application Examples 1-2 and Comparative Application Examples 1-3, wherein (a) is the complex viscosity and (b) is the storage modulus;
[0066] Fig.12The SEM images of the surface and fracture surface of the impact splines prepared by the 3D printed composite materials in Application Examples 1-2 and Comparative Application Examples 1-3 after impact fracture, wherein (a)-(e) are cross-sectional SEM images of PLA / BFs, PLA / BFs / 4NH2-ESO, PLA / BFs / 8NH2-ESO, PLA / BFs / 4NH2-NC514 and PLA / BFs / 8NH2-NC514, respectively, and (a')-(e') are surface SEM images of PLA / BFs, PLA / BFs / 4NH2-ESO, PLA / BFs / 8NH2-ESO, PLA / BFs / 4NH2-NC514 and PLA / BFs / 8NH2-NC514, respectively;
[0067] Fig.13 A comparison diagram of thermoplastic filaments prepared by using the 3D printing composite materials in Application Example 1 and Comparative Application Example 1, wherein the left one is Application Example 1 and the right one is Comparative Application Example 1;
[0068] Fig.14 The printing process and product images of 3D printing of thermoplastic filaments prepared by using the 3D printing composite material in Application Example 1, wherein (a) is 20% of the printing progress, (b) is 40% of the printing progress, (c) is 60% of the printing progress, (d) is 80% of the printing progress, (e) is 100% of the printing progress, and (f)-(g) are product images;
[0069] Fig.15 The heat resistance of the sheet prepared by the 3D printing composite material PLA / BFs / 4NH2-NC514 in Application Example 1 is compared with that of the PLA sheet;
[0070] Fig.16 Schematic diagram of extruding thermoplastic filaments through a single-screw extruder and then performing 3D printing. DETAILED DESCRIPTION
[0071] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0072] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0073] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0074] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0075] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0076] The raw materials and reagents used in the specific implementation of the present invention are all commercially available products. Among them, PLA (4032D) was commercially obtained from NatureWorks in the United States, and the weight average molecular weight (Mw) was 17.62×10 4 g / mol, melt flow rate is 7g / 10min, melting temperature is 190℃, and weight mass in melt index test is 2.16kg; BFs has diameter of 0.1-1μm and length of 5-50μm, purchased from Mujiang Weihua Spice Factory, Shuangshui Town, Xinhui District, Jiangmen City, Guangdong Province, China; NC514 was purchased from Cardolite Corporation of the United States and used directly, with CAS No. 68390-54-5 and weight average molecular weight (Mw) of 537g / mol; BF3NH2Et was provided by Shanghai Sigma-Aldrich; KH550 was purchased from Beijing Mreda; acetone and ethanol were provided by Beijing Chemical Reagent Research Institute Co., Ltd.
[0077] Unless otherwise specified, the "parts" involved in the specific embodiments of the present invention refer to "parts by mass".
[0078] Unless otherwise specified, the "room temperature" referred to in the specific embodiments of the present invention refers to 15-30°C.
[0079] The rotation speed of the "magnetic stirring" involved in the specific implementation manner of the present invention is 150r / min, and the rotation speed of the "violent stirring" involved is 280r / min.
[0080] Example 1
[0081] The preparation steps of NH2-NC514 are as follows:
[0082] S1, dissolving KH550 in an ethanol solution with a volume concentration of 60% (the ethanol solution is a mixture of anhydrous ethanol and deionized water in a volume ratio of 3:2), stirring magnetically for 30 minutes at room temperature to complete the hydrolysis process to obtain hydrolyzed KH550, wherein the dissolved concentration of KH550 in the ethanol solution is 2wt.%;
[0083] S2, dissolving the cationic initiator BF3NH2Et and NC514 in acetone (complete dissolution is sufficient, and there is no specific requirement for the amount of acetone), vigorously stirring at room temperature for 5 minutes to initiate the self-polymerization of NC514 to obtain poly-NC514 (weight average molecular weight is 1395 g / mol after testing), wherein the amount of BF3NH2Et is 2wt.% of the amount of NC514;
[0084] S3. Dissolve poly-NC514 in hydrolyzed KH550, continue magnetic stirring at room temperature for 30 minutes to carry out grafting reaction. After the grafting reaction is completed, dry the reaction solution in a vacuum oven at 80°C for 12 hours to obtain NH2-NC514 (the number average molecular weight is about 8000 g / mol after testing), wherein the mass ratio of hydrolyzed KH550 to poly-NC514 is 1:1.
[0085] Comparative Example 1
[0086] The preparation steps of NH2-ESO are as follows:
[0087] S1, dissolving KH550 in an ethanol solution with a volume concentration of 60% (the ethanol solution is a mixture of anhydrous ethanol and deionized water in a volume ratio of 3:2), stirring magnetically for 30 minutes at room temperature to complete the hydrolysis process to obtain hydrolyzed KH550, wherein the dissolved concentration of KH550 in the ethanol solution is 2wt.%;
[0088] S2, dissolving the cationic initiator BF3NH2Et and ESO (epoxidized soybean oil, weight average molecular weight of about 1000 g / mol) in acetone, and vigorously stirring at room temperature for 5 min to initiate the self-polymerization of ESO to obtain poly-ESO, wherein the amount of BF3NH2Et is 2wt.% of the amount of ESO;
[0089] S3. Dissolve poly-ESO in hydrolyzed KH550, continue magnetic stirring for 30 minutes at room temperature to carry out grafting reaction. After the grafting reaction is completed, dry the reaction solution in a vacuum oven at 80°C for 12 hours to obtain NH2-ESO, wherein the mass ratio of hydrolyzed KH550 to poly-ESO is 1:1.
[0090] The chemical reaction formula for preparing NH2-ESO is as follows Figure 4 As shown, It represents an alkane chain, but it does not represent the same alkane as in the NH2-NC514 structural formula.
[0091] Figure 6 The infrared spectra (FTIR) of NH2-NC514 prepared in Example 1 of the present invention, NH2-ESO prepared in Comparative Example 1, and raw materials NC514 and ESO are shown in FIG. Figure 6 The characteristic peak of carbonyl ester C=O in ESO and NH2-ESO structures can be observed at 1740cm -1 The characteristic peak of the carbon-carbon double bond C=C in the benzene ring skeleton of NC514 and NH2-NC514 structures appears at 1580cm -1 The self-polymerization reaction of ESO and NC514 resulted in the -1 The bending vibration characteristic peak of COC changes, 1030cm -1 The characteristic peak of Si-OC stretching vibration at 3300cm -1 The appearance of the -OH characteristic peak indicates that the hydrolyzed KH550 was successfully grafted onto the surface of poly-ESO and poly-NC514, and NH2-ESO and NH2-NC514 were successfully prepared.
[0092] Application Example 1
[0093] The preparation steps of 3D printing composite materials are as follows:
[0094] S1. Raw material preparation: 70 parts of PLA, 30 parts of BFs, 4 parts of NH2-NC514 (as a compatibilizer) obtained in Example 1;
[0095] S2. PLA, BFs and the compatibilizer were mixed at room temperature at a speed of 60 rpm for 30 min, and then mixed in an internal mixer at a speed of 60 rpm and a temperature of 190° C. for 8 min to obtain a mixed material, which was a 3D printing composite material, recorded as PLA / BFs / 4NH2-NC514.
[0096] Application Example 2
[0097] Compared with Application Example 1, the only difference is that the amount of NH2-NC514 used is 8 parts, and the prepared 3D printing composite material is recorded as PLA / BFs / 8NH2-NC514.
[0098] Comparative application example 1
[0099] Compared with Application Example 1, the only difference is that NH2-ESO prepared in Comparative Example 1 of equal mass is used instead of NH2-NC514 as a compatibilizer, and the prepared 3D printing composite material is recorded as PLA / BFs / 4NH2-ESO.
[0100] Comparative Application Example 2
[0101] Compared with Application Example 2, the only difference is that NH2-ESO prepared in Comparative Example 1 of equal mass is used instead of NH2-NC514 as a compatibilizer, and the prepared 3D printing composite material is recorded as PLA / BFs / 8NH2-ESO.
[0102] Comparative Application Example 3
[0103] Compared with Application Example 1, the only difference is that no compatibilizer is added, and the prepared 3D printing composite material is recorded as PLA / BFs.
[0104] Test Example 1
[0105] BFs were extracted from the 3D printed composite material (2 g) by Soxhlet extraction using chloroform as solvent at 80 °C. After drying at 80 °C for 24 h, the surface microstructure and chemical analysis of the extracted BFs were performed.
[0106] Test method: The changes in the surface microstructure of the extracted BFs were observed using a scanning electron microscope (SEM) on a TESCANVEGA 11 with an accelerating voltage of 10 kV.
[0107] The surface chemical properties of BFs were revealed by X-ray photoelectron spectroscopy (XPS). XPS experiments were performed on an ESCALAB 250Xi XPS instrument with an Al Kα radiation source. Atomic high-resolution spectra were obtained with a pass energy of 70.0 eV and an increment of 0.2 eV. The C1s spectra were analyzed using XPS Peak4.0 software.
[0108] Test results: Test results are as follows Figure 7 and Figure 8 shown.
[0109] Figure 7 The SEM images of BFs extracted from 3D printed composite materials prepared in Application Example 1, Comparative Application Examples 1 and 3, where (a)-(c) are surface SEM images of BFs (extracted from Comparative Application Example 3), BFs / 4NH2-ESO (extracted from Comparative Application Example 1) and BFs / 4NH2-NC514 (extracted from Application Example 1), respectively. Figure 7It can be seen that the BFs without the addition of compatibilizers showed a rough fiber surface, while after adding the compatibilizers NH2-ESO and NH2-NC514, it can be observed that the fiber surface is relatively smooth. This is mainly because during the extraction process, the lignin and hemicellulose on the fiber surface are removed, resulting in the appearance of groove-like indentations. After adding the compatibilizer, the indentations are filled with the formed compatibilizer flexible layer. Since the active groups in the NH2-NC514 structure have higher reactivity with the polar groups on the BFs surface, NH2-NC514 is evenly attached to the BFs surface, and the fiber surface is also smoother.
[0110] The reaction mechanism for preparing 3D printed composite materials (only the chemical sites where the reaction may occur are shown) is as follows Figure 5 As shown in the reaction mechanism of preparing 3D printing composite materials, during the melt compounding process, since NH2-NC514 and NH2-ESO adhere to the surface of BFs and are located at the interface between BFs and PLA matrix, the following reactions mainly occur: (1) The -OH group of BFs can act as a ring-opening agent for the epoxy group in the compatibilizer structure, forming a covalent bond between BFs and the compatibilizer; (2) The -OH group of BFs can undergo a substitution reaction with the -OH group in the compatibilizer structure; (3) The epoxy group in the compatibilizer structure reacts with the terminal -COOH or -OH group of PLA to generate a chemical bond between the compatibilizer and PLA; (4) The amino group in the compatibilizer structure undergoes a substitution reaction with the terminal -COOH group of PLA.
[0111] Figure 8 The curve-resolved XPS C1s spectra of BFs extracted from the 3D printing composite materials prepared in Application Examples 1-2 and Comparative Application Examples 1-3 (BF and BFs in the figure have the same meaning), where (a)-(e) are BFs (extracted from Comparative Application Example 3), BFs / 4NH2-ESO (extracted from Comparative Application Example 1), BFs / 4NH2-ESO (extracted from Comparative Application Example 2), BFs / 4NH2-NC514 (extracted from Application Example 1), and BFs / 4NH2-NC514 (extracted from Application Example 2). Figure 8 It can be seen that natural BFs have four typical C components, namely C1 (CC / CH), C2 (CO), C3 (C=O / OCO) and C4 (OC=O), among which C2 is mainly derived from cellulose, and the other components are closely related to non-cellulose substances such as hemicellulose and lignin. The ratio of C1:C2:C3:C4 in BFs is 1:1.09:0.41:0.03 ( Figure 8(a)). The C component ratio of PLA (the terminal groups of PLA can be ignored) is 1:1:0:1; the NH2-NC514 structure does not contain C3 and C4 components, and the NH2-ESO structure does not contain C3 components, resulting in a decrease in the C3 content with the increase in the amount of compatibilizer, or even disappearance ( Figure 8 (b)-(e)). With the increase of the amount of compatibilizer, the C1 content increases, which may be due to the grafting of the fatty chain in the compatibilizer structure and the -CH3 group of PLA. The C4 content of BFs / 8NH2-NC514 basically disappears due to the uniform attachment of NH2-NC514 on the surface of BFs.
[0112] Test Example 2
[0113] Crystallization performance test
[0114] DSC (Differential Scanning Calorimetry) can measure the crystallinity of polymers. Crystallinity refers to the proportion of crystalline regions in a polymer and is one of the important parameters for evaluating polymer performance. Through DSC testing, the heat changes of polymers during the crystallization process can be measured to evaluate the quality of polymer crystallization performance.
[0115] Test method: TA instrument (TA2500) was used at a N2 flow rate of 50 mL / min. 7 mg of 3D printed composite samples prepared in Application Examples 1-2 and Comparative Application Examples 1-3 were sealed in a covered aluminum pan for testing. For scanning, the sample was heated from 30°C to 200°C at a rate of 10°C / min, and two consecutive scans were tested.
[0116] Test results: Test results are as follows Fig. 9 And as shown in Table 1.
[0117] Table 1DSC crystallization data
[0118]
[0119]
[0120] Fig. 9 The DSC secondary temperature rise curves of the 3D printing composite materials prepared in Application Examples 1-2 and Comparative Application Examples 1-3 (the meaning of BF in the figure is the same as BFs). Fig. 9As shown in Table 1, after modification with the compatibilizer, the glass transition temperature (Tg), melting temperature (Tm) and crystallinity (Xc) of the 3D printed composite material show a downward trend with the increase of the compatibilizer content, and the cold crystallization temperature (Tcc) shows an upward trend, and the change trend of the material with NH2-NC514 as the compatibilizer is more obvious. The reduction of Tg usually means that the material can be transformed from the glassy state to the highly elastic state at a lower temperature, which makes the material easier to deform when subjected to external force, thereby improving the toughness of the material. The reduction of Tm and the increase of Tcc help to reduce energy consumption, reduce production costs and processing difficulties, and improve production efficiency. Lower crystallinity helps to improve the fluidity of the material, making it easier for the material to fill the mold or extruder head during injection molding, extrusion and other processing processes, reducing defects and scrap rates.
[0121] Test Example 3
[0122] Dynamic mechanical analysis
[0123] Test method: The 3D printed composite materials prepared in Application Examples 1-2 and Comparative Application Examples 1-3 were subjected to dynamic mechanical analysis (the composite materials were crushed and prepared into standard specimens with a shape of 40mm×10mm×1mm by a micro injection molding machine for experimental testing) on a DMA7100 TA instrument with a tensile mode of 30-110°C, a heating rate of 2°C / min, and a frequency of 1Hz.
[0124] Test results: The test results are shown in Table 2 and Fig.10 shown.
[0125] Table 2 E' and Tg of 3D printed composites
[0126]
[0127]
[0128] Fig.10 DMA curves of the 3D printed composite materials prepared in Application Examples 1-2 and Comparative Application Examples 1-3 (the meaning of BF in the figure is the same as BFs), where (a) is the storage modulus and (b) is the loss factor. Fig.10It can be seen that when the compatibilizer content is 4 parts, the storage modulus (E') of the composite material is greater than that of the PLA / BFs composite material without compatibilizer modification; when the compatibilizer content is 8 parts, the E' of the composite material is less than that of the PLA / BFs composite material without compatibilizer modification. This is mainly because the epoxy groups in the compatibilizer can react with the polar groups of BFs and the terminal carboxyl groups of PLA to form a cross-linked network polymer. Cross-linking will enhance the rigidity of the material and cause the E' to rise. Excessive compatibilizer can cure in the PLA matrix to form an elastomer, which has a significant effect on the toughness of PLA. The elastomer will destroy the dense structure of the amorphous region of PLA, thereby reducing the E' of the material. The E' value of PLA / BFs / NH2-NC514 is higher than that of PLA / BFs / NH2-ESO. This is because NH2-NC514 can form a network structure with the PLA molecular chain, so that the composite material has a stronger ability to store elastic deformation. For Tg, the DSC (Table 1) method more directly reflects the change in heat capacity of the material during the glass transition process, while DMA focuses on the change in the mechanical properties of the material (especially viscoelasticity). The two methods differ in the test principles, the physical quantities of interest, and the presentation of the curves, but both can effectively measure the Tg of the material. The peak temperature of the loss factor in the DMA test is the Tg of the composite material. The test results are basically consistent with those of DSC. When the compatibilizer content is the same, the Tg of PLA / BFs / NH2-NC514 is lower than that of PLA / BFs / NH2-ESO.
[0129] Test Example 4
[0130] Mechanical properties test
[0131] Test method: After the 3D printed composite material (mixed material obtained after internal mixing) was crushed by a crusher, dumbbell-shaped tensile specimens (GB / T 1040-92) and impact specimens (GB / T 1843-2008) were made by a micro injection molding machine at a barrel temperature of 200°C and a mold temperature of 120°C. The dumbbell-shaped tensile specimens and impact specimens prepared by the 3D printed composite materials in Application Examples 1-3 and Comparative Application Examples 1-3 were placed in a laboratory environment as specimens for 24 hours, and then a tensile test was performed using a universal testing machine according to GB / T1040.2-2006 (IDT ISO 527.2-2:1993), with a tensile speed of 10 mm / min. According to GB / T9341-2008 (IDT ISO 178-2001), a bending test was performed using a universal testing machine, with a test speed of 2 mm / min and a specified deflection of 6 mm. According to the requirements of GB / T 1843-2008 (IDT ISO 180-2000), an unnotched impact test was carried out using an Izod impact testing machine with a 1J hammer.
[0132] Test results: The test results are shown in Table 3.
[0133] Table 3 Mechanical properties of 3D printed composite materials
[0134]
[0135] Strength, toughness, and stiffness are considered key factors in characterizing the mechanical properties of composite materials, and these properties must be carefully balanced when selecting 3D printing materials. However, in most cases, strength and toughness take precedence, especially in various general 3D printing applications. Selecting a material with high strength will ensure that the printed parts have sufficient resistance, thereby minimizing the risk of deformation or breakage. In actual use, components may encounter impacts from different directions and with different intensities. In this case, materials with high toughness can withstand deformation without breaking, thereby achieving superior overall performance. As shown in Table 3, the addition of compatibilizers slightly reduces the strength and stiffness of the composites, and greatly improves toughness. Compared with NH2-ESO, the shorter alkane chain length and higher reactivity of NH2-NC514 enable the composites to achieve a balance between strength and stiffness, which is mainly reflected in the effective coverage of the BFs surface and the entanglement with the PLA matrix molecular chain during processing.
[0136] Test Example 5
[0137] Rheological properties testing
[0138] Test method: The rheological properties of the samples were run on Anton Paar's MCR-502. The temperature was 210°C and 40 points were selected in the range of 0.01-100 rad / s.
[0139] Test results: Test results are as follows Fig.11 shown.
[0140] Fig.11 The rheological properties test curves of the 3D printed composite materials prepared in Application Examples 1-2 and Comparative Application Examples 1-3 (the meaning of BF in the figure is the same as BFs), where (a) is the complex viscosity and (b) is the storage modulus. Fig.11 It can be seen that the melt rheological properties of the composite material are directly related to the degree of dispersion of the fiber in the polymer matrix and the level of interfacial interaction between the fiber and the polymer. The complex viscosity of the PLA / BFs composite without the addition of compatibilizer is lower than that of the composite with the addition of compatibilizer. This is because the compatibilizer can improve the interfacial compatibility of the composite material and increase the degree of entanglement with PLA. The change trend of the storage modulus is basically consistent with the complex viscosity. With the increase of the compatibilizer content, the complex viscosity and storage modulus show an upward trend. This is because the interaction between the compatibilizer and the polymer matrix and bamboo fiber greatly hinders the migration of the polymer chain and the entanglement of the compatibilizer molecular chain itself increases with the increase of the content.
[0141] Test Example 6
[0142] Interface compatibility test
[0143] Test method: The impact fracture surface and surface microstructure changes of the impact spline in Test Example 4 after impact fracture were observed by scanning electron microscopy (SEM), and the observation was performed on TESCAN VEGA 11 with an accelerating voltage of 10 kV. In order to comprehensively evaluate the interfacial bonding strength of 3D printed composite materials and the dispersibility of the compatibilizer in 3D printed composite materials, the 3D printed composite material specimens (impact splines) were immersed in toluene for three days after impact fracture, and the changes in the impact fracture surface and surface microstructure were observed by SEM.
[0144] Test results: Test results are as follows Fig.12 shown.
[0145] Fig.12 The following are SEM images of the surface and fracture surface of the impact splines prepared by 3D printing composite materials in Application Examples 1-2 and Comparative Application Examples 1-3 after impact fracture (the meaning of BF in the figure is the same as that of BFs), wherein (a)-(e) are cross-sectional SEM images of PLA / BFs, PLA / BFs / 4NH2-ESO, PLA / BFs / 8NH2-ESO, PLA / BFs / 4NH2-NC514 and PLA / BFs / 8NH2-NC514, respectively, and (a')-(e') are surface SEM images of PLA / BFs, PLA / BFs / 4NH2-ESO, PLA / BFs / 8NH2-ESO, PLA / BFs / 4NH2-NC514 and PLA / BFs / 8NH2-NC514, respectively. Fig.12 It can be seen that for the 3D printed composite (PLA / BFs) without compatibilizer modification, a large number of deep grooves were generated during the fiber pull-out process, indicating that the interfacial adhesion between BFs and PLA was weak. After adding the compatibilizer, an indistinguishable fiber-matrix interface appeared on the impact fracture surface, confirming that the compatibilizer improved the interfacial bonding of the composite. In contrast, the surface of the sample modified with NH2-NC514 remained relatively smooth after immersion, with no obvious cracks. SEM analysis of PLA / BFs / NH2-ESO after immersion showed that there were a large number of pores in the matrix, which was caused by NH2-ESO leaching. PLA / BFs / NH2-NC514 had fewer cavities in the matrix and no obvious gaps at the interface between PLA and BFs, indicating that PLA / BFs / NH2-NC514 showed enhanced reactivity, in which NH2-NC514 formed chemical bonds with the matrix and BF surface, and remained stable even under long-term solvent exposure, which is consistent with the mechanical properties results discussed above.
[0146] Test Example 7
[0147] Machinability and appearance quality test
[0148] The 3D printed composite materials in Application Example 1 and Comparative Application Example 1 were respectively crushed by a crusher to obtain pellets, which were then fed into a single-screw extruder to form thermoplastic filaments with a diameter controlled at 1.75±0.03 mm. The temperature range of the single-screw extruder was set between 175°C and 180°C.
[0149] Fig.13 The figure is a comparison of thermoplastic filaments prepared by 3D printing composite materials in Application Example 1 and Comparative Application Example 1, wherein the left one is Application Example 1 and the right one is Comparative Application Example 1. Fig.13 It can be seen that the thermoplastic filaments prepared using the 3D printing composite material in Application Example 1 are smooth and have uniform diameter (left side), while the thermoplastic filaments prepared using the 3D printing composite material in Comparative Application Example 1 have an uneven surface (right side), and 3D printing cannot be achieved, resulting in nozzle clogging.
[0150] The thermoplastic filament prepared by the 3D printing composite material in Application Example 1 is used to produce 3D printed products using an FDM printer. During the FDM printing process, the thermoplastic filament is transformed into a viscous flow state and extruded layer by layer from the nozzle onto the support platform. The FDM printer parameters are set as follows: nozzle temperature 210°C, platform temperature 80°C, printing speed 40mm / s, layer thickness 0.1mm, and a 3D printed product is obtained. The printing process and the printed product are shown in the figure below. Fig.14 The schematic diagram of the thermoplastic filament extruded by a single screw extruder and then 3D printed is shown in Fig.16 shown.
[0151] Fig.14 The printing process and product pictures of 3D printing of thermoplastic filaments prepared by using the 3D printing composite material in Application Example 1, wherein (a) is a printing progress of 20%, (b) is a printing progress of 40%, (c) is a printing progress of 60%, (d) is a printing progress of 80%, (e) is a printing progress of 100%, and (f)-(g) are product pictures. Fig.14 The 3D printing process and product pictures of PLA / BFs / 4NH2-NC514 are shown, which shows that PLA / BFs / 4NH2-NC514 bio-based composite materials can produce not only simple solid structures, but also complex thin-walled hollow structures without the need for support structures and platform accessories. The printing process is smooth and the model appearance is good.
[0152] Fig.15In order to compare the heat resistance of the sheet prepared by 3D printing composite material PLA / BFs / 4NH2-NC514 in Application Example 1 and the PLA sheet (a thin square sheet sample with a side length of 10 mm and a thickness of 4 mm prepared by 3D printing), Fig.15 It can be seen that after the pure PLA sheet was heated at 80℃ for 30min, the sheet (edge area) underwent irreversible deformation. In contrast, under the same conditions, the sheet prepared by PLA / BFs / 4NH2-NC514 had no obvious thermal deformation, indicating that the durability against thermal deformation was enhanced. And according to the test, compared with pure PLA, the density of PLA / BFs / 4NH2-NC514 (from 1.31g / cm 3 Down to 1.28g / cm 3 ) and water absorption (from 1.1% to 0.65%) were reduced, indicating that PLA / BFs / 4NH2-NC514 is more durable than PLA, with the additional benefit of reduced raw material consumption, and can be used to manufacture products of equivalent volume.
[0153] The determination of water absorption rate refers to GB / T 1034-2008. The sample is dried in an oven at 50°C for 24 hours, cooled to room temperature in a desiccator, and weighed (mass m1). The sample is soaked in distilled water at 23°C for 25 hours, then taken out, the surface water stains are wiped off, and weighed again (mass m2). The water absorption rate (C) of the sample can be expressed as:
[0154]
[0155] The density is determined in accordance with GB / T 1033.1-2008. Weigh the sample with the metal wire suspended in the air, immerse the sample with the metal wire suspended in a beaker filled with distilled water on a fixed bracket, and weigh the sample in the distilled water. The density of the sample (ρ S ) can be expressed as:
[0156]
[0157] Among them, ρ S is the density of the sample, m S,A is the mass of the sample in air, m S,IL is the apparent mass of the sample, ρ IL is the density of distilled water.
[0158] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. An amination epoxy cardanol glycidyl ether, characterized in that: The structural formula is: in, Represents -(CH2)6-.
2. A method for preparing the amino epoxy cardanol glycidyl ether as claimed in claim 1, characterized in that: The following steps are involved: hydrolyzing KH550 to obtain hydrolyzed KH550; The self-polymerization of NC514 was initiated by a cationic initiator to obtain poly-NC514; The poly-NC514 and the hydrolyzed KH550 are used as reactants to carry out a grafting reaction to obtain the amino epoxy cardanol glycidyl ether.
3. The preparation method according to claim 2, characterized in that: The step of hydrolyzing KH550 comprises: dissolving KH550 in an ethanol solution, magnetically stirring for 30-90 minutes, completing the hydrolysis reaction, and obtaining the hydrolyzed KH550; The KH550 is dissolved in the ethanol solution at a concentration of 2 wt.%.
4. The preparation method according to claim 2, characterized in that: The step of initiating the self-polymerization of NC514 using a cationic initiator comprises: Dissolving the cationic initiator and NC514 in a solvent, and vigorously stirring at room temperature for 5-10 minutes to initiate self-polymerization of NC514 to obtain the poly-NC514; The cationic initiator is BF3NH2Et; The amount of the cationic initiator used is 1-2 wt.% of the amount of NC514 used.
5. The preparation method according to claim 2, characterized in that: The step of carrying out a grafting reaction using poly-NC514 and the hydrolyzed KH550 as reactants comprises: dissolving the poly-NC514 in the hydrolyzed KH550, stirring for 30-60 minutes, completing the grafting reaction, and obtaining the amino epoxy cardanol glycidyl ether; The mass ratio of the poly-NC514 to the hydrolyzed KH550 is 3-1:1-3.
6. A use of the amino epoxy cardanol glycidyl ether as claimed in claim 1 as a compatibilizer in the preparation of 3D printing composite materials.
7. A 3D printing composite material, characterized in that: Calculated by weight, the raw materials include: 70 parts of PLA, 30 parts of BFs and 2-8 parts of a compatibilizer; the compatibilizer is the amino epoxy cardanol glycidyl ether according to claim 1.
8. A method for preparing a 3D printing composite material as claimed in claim 7, characterized in that: The following steps are involved: PLA, BFs and a compatibilizer are first mixed at room temperature and then mixed by internal kneading to obtain the 3D printing composite material.
9. A method for preparing a 3D printed product using the 3D printed composite material according to claim 7, characterized in that: The following steps are involved: The 3D printing composite material is crushed and then melt-extruded to obtain thermoplastic filaments; the thermoplastic filaments are 3D printed to obtain 3D printed products.
10. A 3D printed product obtained by the preparation method according to claim 9.
Citation Information
Patent Citations
Thermoplastic composites comprising water-soluble PEO graft polymers useful for 3-dimensional additive manufacturing
CA2978556A1
Bamboo fiber reinforced polylactic acid composite material used for 3D printing and preparation method for bamboo fiber reinforced polylactic acid composite material
CN104927320A
Reactive compatibilized bamboo fiber / polylactic acid composite material and preparation method thereof
CN109467897A
Preparation of epoxy cardanol-based chain extender modified PBAT-PLA composite film
CN115058103A
Solvent-free bio-based environment-friendly coating
CN115678379A